Effet du plomb sur la germination des graines de Cleome amblyocarpa Barr.& Murb - CHAMOUMA, Fethia; GHEDDAB, Nadjiya (My University, 2020)
Lead (Pb) is a heavy metal that is highly toxic to plants, animals and humans. it currently poses significant problems in terms of environmental contamination. Plants, because of their immobility, are particularly exposed.The purpose of this study was to evaluate the effect of lead stress on seed germination and seedling growth of Cleome amblyocarpa Barr. & Murb. Seeds were germinated in the presence of lead nitrate Pb(NO3)2 at various concentrations (0, 50, 100, 150, 200 and 250ppm) and under controlled conditions (temperature 26°C and darkness) for 15 days. The results obtained showed that scarified seeds of Cleome amblyocarpa Barr. & Murb are characterized by a good germination ability at low lead concentrations. The length of seedling stems and rootlets and the tolerance index decrease considerably with increasing lead levels. The increase in Pb levels significantly increases the percentage of phytotoxicity along the length of the roots of Cleome amblyocarpa Barr. & Murb. The tolerance threshold is below 150 ppm Pb(NO3)2. Above this level, the germinative power declines and the toxic effect increases proportionally with the increase in the concentration of the metallic trace element.
Keywords: Lead; metallic stress; Cleome amblyocarpa Barr.; Murb; Germination.